Evaluasi Kelayakan Bisnis Di Restoran Sangkuriang Bandung Dari Aspek Operasional - Unggul Pramesti, Dhini; Sudono, Agus; Ridwanudin, Oce (Gastronomy Tourism Journal, 2016)
Evaluate the feasibility has been widely known by the public, especially peoplewho are engaged in the business world. This experiment aims to determine thefeasibility evaluation overview Sunda and Oriental Restaurants in Bandung, which in terms of feasibility operasional.Evaluasi aspects needed to see a picture of decent atu not like a business to run.The method used is descriptive qualitative research methods. Methods of datacollection is done by conducting interviews and observations. Sampling technique used is nonprobability. Data analysis technique used is the SWOT matrix with IE matrix analysis, IFAS and EFAS. Based on the research results, obtained that picture business viability in Bandung Restaurant Sangkuriang declared eligible.Results of internal and external factors in the operation were at high levels. Theoperational aspects of the matter Weight gain by 3.13 SWOT Matrix internal factors and external factors, which means 3,07 Sangkuriang Bandung Restaurant is eligible to run.